2007
DOI: 10.1590/s0100-29452007000100014
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e respiração de crescimento em frutos de Psidium cattleyanum sabine durante o ciclo de desenvolvimento

Abstract: RESUMO-O experimento foi conduzido em condições de campo, sendo os frutos colhidos em araçazeiros de seis anos, crescidos no pomar da EMBRAPA-Clima Temperado. O objetivo foi determinar a composição química, a eficiência de conversão da glicose em novos compostos e a estimativa da respiração de crescimento de araçá ao longo da ontogenia do fruto. Os teores de macronutrientes decresceram ao longo do desenvolvimento do fruto. Os conteúdos de amido, carboidratos solúveis totais, açúcares redutores, lipídeos e ácid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
0
14
0
8
Order By: Relevance
“…Con ello, queda confirmado que en la respiración, los compuestos altamente energéticos (ATP) y reductores (NADH 2 ) son formados a partir de la oxidación de carbohidratos, para ser utilizados en la síntesis de nuevas sustancias (Galho et al, 2007) durante el desarrollo del fruto.…”
Section: Intensidad Respiratoriaunclassified
“…Con ello, queda confirmado que en la respiración, los compuestos altamente energéticos (ATP) y reductores (NADH 2 ) son formados a partir de la oxidación de carbohidratos, para ser utilizados en la síntesis de nuevas sustancias (Galho et al, 2007) durante el desarrollo del fruto.…”
Section: Intensidad Respiratoriaunclassified
“…It's an arboreal species that produces a fleshy fruit with peculiar taste, possessing a rich chemical composition (Galho, Lopes, Bacarin, & Limac, 2007), a large variety of bioactive compounds, such as phenolics and carotenoids (Silva, Rodrigues, Mercadante, & De Rosso, 2014), as well as essential oils and other volatile compounds of pharmacological interest (Marin et al, 2008). Previous studies have already determined that aqueous and ketone extracts from the Red Strawberry Guava generate various antioxidant activities, have an anti-proliferative effect on human cancer cells, and acts as an antimicrobial agent against Salmonella enteritidis (Medina et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary exploratory studies suggested high antioxidant activity and high phenolic content differing among araçá genotypes (Medina et al, 2011). The few investigations of araçá suggest nutritional and functional potential (Galho et al, 2007). Although traditionally appreciated for its sensory attributes and expected functional properties, araçá is still poorly characterized, and limited scientific information is available about the fruit.…”
Section: Introductionmentioning
confidence: 99%